2007
DOI: 10.1103/physrevb.75.092404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain and electric field on the electronic soft matter in manganite thin films

Abstract: We have studied the effect of substrate-induced strain on the properties of the hole-doped manganite (La1−yPry)0.67Ca0.33MnO3 (y = 0.4, 0.5 and 0.6) in order to distinguish between the roles played by long-range strain interactions and quenched atomic disorder in forming the micrometerscale phase separated state. We show that a fluid phase separated (FPS) state is formed at intermediate temperatures similar to the strain-liquid state in bulk compounds, which can be converted to a metallic state by applying an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
102
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(107 citation statements)
references
References 22 publications
5
102
0
Order By: Relevance
“…An important feature of the resistance anisotropy is that it is observed only during the cooling cycle. It has been shown that the FPS state in which the FMM regions behave in a dynamic, fluid-like fashion, occurs only during the cooling cycle [7,12]. Such dynamic behavior in the phase coexistence region has also been observed using magnetization, noise, and neutron diffraction measurements [25][26][27].…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…An important feature of the resistance anisotropy is that it is observed only during the cooling cycle. It has been shown that the FPS state in which the FMM regions behave in a dynamic, fluid-like fashion, occurs only during the cooling cycle [7,12]. Such dynamic behavior in the phase coexistence region has also been observed using magnetization, noise, and neutron diffraction measurements [25][26][27].…”
mentioning
confidence: 81%
“…In addition, theoretical calculations have also shown that an electric field can lead to anisotropic resistivity and CER in the phase separated state of manganites [16,19]. We observed the DEP-like behavior only in the fluid phase separated (FPS) region of the (La 0.4 Pr 0.6 ) 0.67 Ca 0.33 MnO 3 (LPCMO) phase diagram which corresponds to the same region of the phase diagram where strong electric field effects have been observed before [12,13,20]. On the other hand, in the glassy, static phase separated (SPS) region where the electric field effects are weak, DEP-like behavior is not observed.…”
mentioning
confidence: 83%
See 3 more Smart Citations